(untitled) (Annals of Medical Research, 2021)
Aim: Kidney stones are one of the most common diseases around the world. Used together with Extracorporeal Shockwave Lithotripsy (ESWL), Retrograde Intrarenal Surgery (RIRS) is the most common method used for kidney stones below 2 cm. The purpose of our study is to evaluate the safety and efficacy of RIRS in aging male patients with kidney stones.Material and Methods: Our study contains 213 patients who underwent RIRS in Beylikduzu State Hospital between March 2017 and March 2019. Patients were examined retrospectively and divided in four groups according to their age [(between 40 and 49 for Group 1), (between 50 and 59 for Group 2), (between 60 and 69 for Group3), (70 and above for Group 4)]. Demographic data, stone size and location, and American Society of Anesthesiologist (ASA) scores of patients have been recorded. Stone-free rate at postoperative month 3, hospitalization period, double J (DJ) stenting period, ESWL, or whether they have had a second operation have been recorded. ANOVA, Chi-Square tests were used in statistical analysis.Results: Stone characteristics and demographic data of four groups have been examined. Stone size was similar. ASA scores increased with increasing age as expected (p=0.001). Patients had similar mean operation period, hospitalization period and DJ stenting duration, and no statistically significant difference was detected (p>0.05). Upon examining stone-free rate at postoperative month 3, still no statistically significant difference was determined (p>0.05). There was no need for perioperative blood transfusion. Conclusion: These results show that RIRS is an efficient and safe method in elderly male patients with kidney stones. Well-designed studies with large scales are required for the confirmation of this study.